DIAGNOSTIC OF THE INSULATION STATE OF THE ASYNCHRONOUS MOTOR AND THE POWER SUPPLY CABLE UNDER CONDITIONS OF LOCAL COMPENSATION - V. E. Krivonosov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
More than 70 % of the load in metallurgy, mining, gas, and other industries of the CIS consist of asynchronous motors. A relevant objective for all enterprises is to reduce consumption of reactive power in the network and ensuring reliable start of the engine by controlling the resistance value of the insulation. The most effective measure for reactive power compensation is placing the capacitor batteries directly at the points of connection of the asynchronous motor i. e. local reactive power compensation. The aim of the present research was to reduce the cost of production of the enterprise (which provides reactive power compensation), and in the period of technological pause to use the power stored in the capacitor to batteries in order control the changes of resistance value of insulation. After disconnecting the motor from the mains and its stop, the windings is being connected in parallel to the capacitor bank. The discharge of the capacitor is performed in the circuit consisting of the inductance of the motor winding, the integrated insulation resistance and battery capacity. Characteristic features of the transitional discharge process of the capacitor depend on the size of the equivalent circuit elements. The transition process may be aperiodic and periodic in its nature. Aging of motor winding causes a decrease of its impedance. When the magnitude of the insulation resistance reaches a critical value, this causes a change of the nature of the process. The device that has been developed monitors the insulation condition of the motor and the power supply cable during technological pauses without the low voltage power source and additional switching.